Callus induction and withanolides production through cell suspension culture of Withania coagulans (Stocks) Dunal - Mohammad Hossein Mirjalili; Hassan Esmaeili (Institue of Medicinal Plants, ACECR, 2022)
Background: Withania coagulans (Stocks) Dunal is a well-known medicinal plant due to its many healing properties. Objective: The aim of the present study was to induce friable callus and subsequently establish the plant cell suspension cultures for the production of two important withanolides i.e. withaferin A (WFA) and withanolide A (WNA). Methods: In vitro callus induction was carried out from young leaf and internodal explants cultured on MS medium fortified with various concentrations (0, 1.0, 1.5, 2.0 and 2.5 mg/L) of auxins (2,4-D, NAA, and IAA) solely or in combination with BAP (0., 0.5 and 1.0 mg/L) in a factorial experiment based on a completely randomized design with five replications. The plant cell culture was then established for the production of both withanolides. Results: The percentage of callogenesis from the leaf (25.0-96.0 %) was higher than internodal explants (23.2-85.4 %). The high percentage of friable calli was achieved from leaf explants cultured on MS medium fortified with 2.5 mg/L 2,4-D + 0.5 mg/L BAP. Cell suspension culture was established from derived friable callus cultured on MS medium supplemented with 1.5 mg/L IAA + 0.5 mg/L BAP. The highest accumulation of biomass (172 g/L fresh weight and 15 g/L dry weight) and the production of both withanolides were observed in the fourth week of the culture period. The plant cells produced 0.08 and 21 µg/L WFA and WNA at this time, respectively. Conclusion: These results can be used for future research on biosynthesis pathways of withanolides as well as their production in bioreactors.